ANALISIS BENTUK MUSIK DAN MAKNA LIRIK LAGU “GOODNESS OF GOD” KARYA JENN JOHNSON DAN BETHEL MUSIC - Kharis Noel Batuara; Dwi Sutrianto (Universitas Kristen Immanuel, 2024)
This article delves into the intricate interplay between music and lyrical meaning in the song